Pengelolaan Rekam Medis Inaktif Di RSUD Ulin Banjarmasin - Nina Rahmadiliyani; Wiliyanor Wiliyanor (Jurnal Kesehatan Indonesia, 2018)
Inactive Medical Record is a medical record document that reaches for 5 years and never used to visit health service. Often the storage of inactive medical records is not properly managed. Many inactive medical record documents are stored and stacked on the floor because of insufficient shelf capacity.The purpose of this study is to understand the management of inactive medical records In ulin banjarmasin hospitals.The method used in this research is qualitative descriptive.The study subjects were inactive medical record storage officer, which consisted of a medical record head and two storage officers. Storage of inactive medical records is on the 6th floor and active medical records are on the 2nd floor, outpatient and inpatient are combined, on retention of inactive medical records are not stored in the form of microfilm and disk but stored in books and computer. In medical record room, there is no room temperature control, there is no humidity control room, and light arrangement of room using lamp. Maintenance of the record room cleaning inactive medical record storage is done by cleaning service, on the exchange of air through the door. There is no maintenance of the inactive medical record file, such as hygiene, air exchange and medical record control. In today's inactive medical record storage still uses a centralized system and an active medical record file using a decentralized system. The requirements of inactive medical record storage room on temperature control, storage shelves and humidity of the room do not use air conditioner. And there is no control on the maintenance of inactive medical records files such as cleanliness, air exchange.